Utilization of bottom ash for alkali-activated (SI-AL) materials: a review - Abdul Kadir, Aeslina; Yahya, Zarina; Hussin, Kamarudin; Liew, Yun Ming; Abdullah, Mohd Mustafa Al Bakri; Deraman, Laila Mardiah (Asian Research Publishing Network (ARPN), 2015)
In Malaysia, 180 tons/day of solid waste bottom ash are produced by a Tanjung Bin power station, which is one of the four coal power plants in Malaysia. Hence, to overcome this problem, the solid waste could be used as source material in construction industry using geopolymer technique. Alkali-activated materials are introduced as an alternative materials to ordinary Portland cement (OPC) in the construction industry. There are many types of alkaline activator raw materi als such as bottom ash, fly ash, metakaolin and so on that can be substituted the materials existing such as cement and fine or course aggregate in the market now to make any production where the materials are coming from waste.The geopolymerization process involves a substantially fast chemical reaction under alkaline conditions with Si and Al minerals that results in a three‐dimensional polymeric chain and ring structure consisting of Si‐O‐Al‐O. The higher Si‐O‐Al‐O bonds are contained in the geopolymer, the higher compressive strength results will find. Several types of building materials such as"